1978
DOI: 10.1073/pnas.75.10.5090
|View full text |Cite
|
Sign up to set email alerts
|

Extent of genetic variation at a highly polymorphic esterase locus in Drosophila pseudoobscura.

Abstract: The esterase-5 locus of Drosophila pseudoobscura has been screened for variation by using a wide variety of electrophoretic conditions and by testing heat sensitivity.Among 50 isogenic lines from 17 popua ions, 21 genetic variants were found at the locus, 18 by electrophoresis and 3 by heat denaturation. Including alleles previously known, there are a total of 30 alleles at this locus in natural populations. This represents a doubling of the previous estimates of polymorphism at this locus. The study confirms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…With the standard technique they used, they may have seen only a fraction of the total variants (Coyne et al, 1978). Nevertheless it is completely clear that the coding sequence differences leading to amino acid replacement in even highly polymorphic proteins share only the smallest part of the single copy DNA variation.…”
Section: Comparison Of Protein Andmentioning
confidence: 99%
See 1 more Smart Citation
“…With the standard technique they used, they may have seen only a fraction of the total variants (Coyne et al, 1978). Nevertheless it is completely clear that the coding sequence differences leading to amino acid replacement in even highly polymorphic proteins share only the smallest part of the single copy DNA variation.…”
Section: Comparison Of Protein Andmentioning
confidence: 99%
“…No estimate of silent differences comes from these measurements. The total variation (Quid be somewhat larger since the technique detects only a fraction of the total amino acid differences (Coyne et al, 1978).…”
Section: Comparison Of Protein Andmentioning
confidence: 99%
“…The observed unevenness of electromorph frequencies (COYNE et al 1978), however, puts this explanation as well as other explanations of balancing selection into serious difficulties . We, thus, have a paradox.…”
Section: The Modelmentioning
confidence: 87%
“…This simple heuristic model of random drift of neutral or nearly-neutral mutations within isofitness alleles of a balanced polymorphism needs to be quantified in order to test its predictions against predictions of the neutral and nearly-neutral models of classical or monomorphic loci. By providing a mechanism for reaching a neutral-theory equilibrium, this model may explain better the great number of rare electromorphs revealed at Group I1 loci (COYNE et al 1978) as well as the greater dichotomy between Group I and Group I1 loci revealed by variable electrophoresis conditions (COYNE and FELTON 1977;BECKENBACH and PRAKASH 1977) than do neutrality models of monomorphic loci.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation